The Politeness Requesting Principle Found in “Titanic” TV Mini Series - Putra, I Komang Tris Prasetya Wahyudi; Agung, I Gusti Ayu Mahatma (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2023)
The purpose of this study is to investigate the strategy used in the Titanic television series for making politeness requests. In the course of this research, a descriptive qualitative methodology was utilized. The Titanic television series, which was directed by Robert Lieberman and broadcast in 1996, served as the source of the data. The information was gathered by going on YouTube and watching episodes of the Titanic television series. The data were analyzed by applying the theory that Brown and Levinson had proposed (1987). The findings demonstrated that the characters utilized strategies of politeness in order to lessen the likelihood of a threat to their own self-image. The research uncovered four distinct forms of politeness: bald on record, bald off record, positive politeness, and negative politeness.